PENGARUH PERSEPSI, PENGETAHUAN AKUNTANSI DAN PENGHARGAAN FINANSIAL TERHADAP MINAT MAHASISWA UNTUK BERKARIR DI BIDANG AKUNTAN PUBLIK - Giovany Raeng Sugi Saba Tambing; I Gusti Ayu Nyoman Budiasih (JIEKA: Jurnal Integrasi Ekonomi, Keuangan, dan Akuntansi, 2025)
This study aims to analyze the influence of perception, accounting knowledge, and financial rewards on accounting students’ interest in pursuing a career as public accountants. The research was conducted among students of the Accounting Study Program, Faculty of Economics and Business, Udayana University, using a quantitative research design. The study population consisted of 2022 cohort students who had completed the Auditing 1 and Auditing 2 courses. Through purposive sampling, a total of 180 respondents were obtained in accordance with the established criteria. Data were collected using a questionnaire employing a 1– 5 Likert scale designed to measure students’ perceptions, levels of accounting knowledge, perceived financial rewards, and interest in becoming public accountants. The collected data were analyzed using multiple linear regression with the assistance of SPSS 26 to determine the effect of each independent variable on the dependent variable. The results indicate that perception, accounting knowledge, and financial rewards all have a positive influence on students’ interest in choosing a career as public accountants. These findings suggest that more favorable perceptions, stronger accounting knowledge, and higher expected financial rewards lead to greater student interest in the public accounting profession. This study contributes to the existing accounting literature and provides valuable insights for students in considering their future career decisions.